Eleven Year Epidemiological Study of Tuberculosis in Golestan Province, Northern of Iran - Mohammad Reza HONARVAR; Abdurrahman CHARKAZI; Kamal MIRKARIMI; Mahnaz SHEIKHI; Hamid Reza KAMALINIA; Elahe RAHIM ARBABI (Tehran University of Medical Sciences, 2020)
Background: At present, researchers were aimed at exploring the epidemiology of tuberculosis (TB) in Golestan Province in North of Iran that usually ranks 2nd or 1st, alternatively. Methods: An epidemiological study of 11 years was carried out over 8405 patients with TB from 2005 to 2014 years. Data were collected from Health System of the Ministry of Health in Iran using a patient- sheet. Descriptive statistics were applied to report the results. Results: Of those screened, the vast majority of patients with newly diagnosed smear-positive 1799 (41.6%) and smear-positive with relapse 203 (56.5%) were referred from Health System (outpatient cases). Given the newly diagnosed TB, 3559 and 264 of smear-positive were treated and died, respectively; while, 1196 and 119 of smear-negative cases were accordingly treated completely and died. Conclusion: The vast majority of TB cases are infected by pulmonary TB, educational preventive programs seem likely more useful to control the disease.